Multivector Nature of the Eurаsian Integration Process - Vladimir Alexandrovich Shamakhov (Управленческое консультирование, 2018)
In the article is characterized the multi-vector of the Eurasian integration in the context of global trends of modern development. One of the key directions of cooperation within the framework of Eurasian integration now is the Eurasian Economic Union - «The economic belt of the Silk Road». Such collaboration involves the development of not only the economy or transport, but also a new relationship in various forms of public diplomacy as an important mechanism for the formation of international strategic partnership within the Eurasian space in the long term.